Photoluminescence enhancement and quenching of ZnS:Mn2+ in the presence of Au and Ag nanoparticles synthesized by pulse laser ablation in solution. - Duc, Tran Trong; Van, Bui Hong; Binh, Nguyen The (VNU Journal of Science: Mathematics - Physics; Vol 38 No 3DO - 10.25073/2588-1124/vnumap.4708, 2022)
Abstract : Gold (Au) and silver (Ag) nanoparticles were synthesized by laser ablation in water. The average sizes of Au and Ag nanoparticles are 18,4 nm and 21,8 nm respectively. ZnS:Mn 2+ nanoparticles with average size of 3-5 nm were prepared by a co-precipitation method. The photoluminescence of ZnS:Mn 2+ solution in mixture with Au (Ag) nanoparticle colloids was investigated. The quenching effect on Mn 2+ emission at 601 nm band were observed in the presence of the Au and Ag nanoparticles while the D-A emission at 445 nm band was enhanced and blue shifted by Au nanoparticles . The results and discussion are presented in this report.